David Shambaugh, China Goes Global. The Partial Power, Oxford-Nueva York, Oxford University Press, 2013, 432 pp. - Haro, Francisco (Estudios de Asia y África, 2014)
David Shambaugh, China Goes Global. The Partial Power, Oxford-Nueva York, Oxford University Press, 2013, 432 pp.